Understanding the patient journey to the Emergency Department – A South Australian study. Issue 2 (May 2015) - Robinson, Craig; Verrall, Claire; Houghton, Liza; Zeitz, Kathryn
Summary Background To determine patients' points of contact prior to or decision making processes before presenting to an Emergency Department for treatment. To obtain data that may inform future exploration of targeted Emergency Department avoidance strategies. Method All patients presenting to two metropolitan Emergency Departments over a 24 h period were surveyed. Where information was unattainable, it was sought from computerised Patient Administration Systems used by each Emergency Department. A descriptive analysis of the results was undertaken. Results Three hundred and thirty two patients presented over the 48 h survey period. Results showed that 200 (60.2%) were self-referred, 65 patients (19.6%) contacted their general practitioner, 22 (6.6%) were transferred from other hospitals and 3 patients (0.9%) contacted the National Healthdirect Australia triage hotline prior to presenting to the Emergency Department. Conclusion The study showed 39.8% had sought advice from other health care professionals prior to presenting to the Emergency Department and that 60.2% of patients were self-referred. This study has not revealed any new pathways that warrant targeting for Emergency Department avoidance strategies. The focus still needs to target primary care referrals, ambulance service transports and smaller hospital transfers.